Safety of vaccines used for routine immunization in the United States: An updated systematic review and meta-analysis. Issue 28 (23rd June 2021) - Gidengil, Courtney; Goetz, Matthew Bidwell; Newberry, Sydne; Maglione, Margaret; Hall, Owen; Larkin, Jody; Motala, Aneesa; Hempel, Susanne
Highlights: Understanding the safety of vaccines is critical to inform decisions about vaccination. Included comparative studies reported the presence or absence of adverse events. Across a large body of research we found few associations of vaccines and serious key adverse events. Abstract: Background: Understanding the safety of vaccines is critical to inform decisions about vaccination. Our objective was to conduct a systematic review of the safety of vaccines recommended for children, adults, and pregnant women in the United States. Methods: We searched the literature in November 2020 to update a 2014 Agency for Healthcare Research and Quality review by integrating newly available data. Studies of vaccines that used a comparator and reported the presence or absence of key adverse events were eligible. Adhering to Evidence-based Practice Center methodology, we assessed the strength of evidence (SoE) for all evidence statements. The systematic review is registered in PROSPERO (CRD42020180089). Results: Of 56, 603 reviewed citations, 338 studies reported in 518 publications met inclusion criteria. For children, SoE was high for no increased risk of autism following measles, mumps, and rubella (MMR) vaccine. SoE was high for increased risk of febrile seizures with MMR. There was no evidence of increased risk of intussusception with rotavirus vaccine at the latest follow-up (moderate SoE), nor of diabetes (high SoE). There was no evidence of increased risk or insufficient evidence for key adverse events for newer vaccines such as 9-valent human papillomavirus and meningococcal B vaccines. For adults, there was no evidence of increased risk (varied SoE) or insufficient evidence for key adverse events for the new adjuvanted inactivated influenza vaccine and recombinant adjuvanted zoster vaccine. We found no evidence of increased risk (varied SoE) for key adverse events among pregnant women following tetanus, diphtheria, and acellular pertussis vaccine, including stillbirth (moderate SoE). Conclusions: Across a large body of research we found few associations of vaccines and serious key adverse events; however, rare events are challenging to study. Any adverse events should be weighed against the protective benefits that vaccines provide.